Self-financing Tax/Subsidy Mechanisms in Environmental Regulation with Many Firms - Jörg Breitscheidel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We consider the application of self-financing tax/subsidy mechanisms in environmental regulation and explore the question whether these mechanisms yield strong investment incentives in a market with many firms under Cournot competition. It turns out that the tax/subsidy mechanism with the announcement of the subsidy rate and the tax/subsidy mechanism with the announcement of the tax rate work for an arbitrary number of firms, which means that they yield strong incentives for investing in environmentally friendly technologies. The announcement of the subsidy rate is preferable for solving hold-up problems.
Keywords: Q28; L50; D62; D43; 330; Hold-up problems; Environmental regulation; Taxes and subsidies; Selffinancing mechanisms; Emission control; Umweltschutzinvestition; Umweltpolitik; Umweltabgabe; Subvention; Steueraufkommen; Wohlfahrtseffekt; Theorie; hold-up problems